2007
DOI: 10.1007/s10584-007-9324-6
|View full text |Cite
|
Sign up to set email alerts
|

A high-quality monthly pan evaporation dataset for Australia

Abstract: A high-quality monthly pan evaporation dataset of 60 stations has been developed for monitoring long-term pan evaporation trends over Australia. The quality control process involved examination of historical station metadata together with an objective test comparing candidate series with neighboring stations. Identified points of discontinuity were located, including installations of bird guards, site relocations and changes in exposure. Appropriate inhomogeneity adjustments have been applied using established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 27 publications
3
51
1
Order By: Relevance
“…Appropriate inhomogeneity adjustments were applied using established methods to produce the first homogeneous pan evaporation dataset for Australia. Analysis of these data reveals that Australian annual mean pan-evaporation shows large interannual variability with no trend over the 1970-2005 period (Jovanovic et al 2008). Previous studies using unadjusted data had shown a decline in pan evaporation (e.g.…”
Section: No Universal Pan Evaporation Trendmentioning
confidence: 87%
See 2 more Smart Citations
“…Appropriate inhomogeneity adjustments were applied using established methods to produce the first homogeneous pan evaporation dataset for Australia. Analysis of these data reveals that Australian annual mean pan-evaporation shows large interannual variability with no trend over the 1970-2005 period (Jovanovic et al 2008). Previous studies using unadjusted data had shown a decline in pan evaporation (e.g.…”
Section: No Universal Pan Evaporation Trendmentioning
confidence: 87%
“…A highquality monthly pan evaporation dataset of 60 stations has been developed for monitoring long-term pan evaporation trends over Australia (Jovanovic et al 2008). The quality control process involved examination of historical station metadata together with an objective test comparing candidate series with neighbouring stations.…”
Section: No Universal Pan Evaporation Trendmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship is strongest during spring and summer. Jovanovic et al (2008) found a near-zero trend in all-Australian pan evaporation over 1970-2005, despite a clear signal of atmospheric warming over this time. It has been suggested that decreases in solar radiation, or a decline in mean wind speed, may have offset the influence of a warmer atmosphere and reduced relative humidity.…”
Section: Comparison With Pan Evaporationmentioning
confidence: 82%
“…However, the potential for large discontinuities exists due to the subjective nature of the recordings. Several Australian high-quality (homogenised) climate datasets have been developed to identify, monitor and attribute changes in elements such as rainfall (Lavery et al 1992), temperature (Torok and Nicholls 1996;Della-Marta et al 2004) and pan evaporation (Jovanovic et al 2008). These datasets have been produced using a variety of quality control and correction techniques.…”
Section: Identification Of Data Inhomogeneitiesmentioning
confidence: 99%